Transformative climate governance in small Swedish municipalities: Exploring the cases of Enköping and Kiruna - Anna Kronvall; Wolfgang Haupt; Kristine Kern (Environmental Policy and Governance, 2023)
Local authorities are important actors in sustainability transformations, but smaller municipalities generally do not have the same capacities as larger ones to work strategically with climate-related risks and long-term sustainability issues. Our study analyses the efforts of two Swedish local authorities to build capacity for transformative climate governance, paying attention to how structural factors and multi-level governance relations shape local capacity building. Drawing on interviews with municipal staff and the analysis of policy documents we show that both local authorities are increasingly applying experimental climate governance approaches. In Enköping, innovative governance processes support sustainability objectives and promote public–private collaboration. In Kiruna, the necessity to move the town centre has advanced innovation capacity but steals attention from other issues. We conclude that vertical and horizontal multi-level governance relations facilitate capacity building, but in a national context where climate action is largely voluntary, more support is needed for smaller municipalities with limited resources to reach their climate goals.
Keywords: 330; capacity-building; climate change adaptation; climate change mitigation; experimental governance; local authorities; multi-level governance; sustainability transformations